Analysis of Factors that Influence Prospective New Students to Choose a Tourism Study Program at Universities in Yogyakarta - Sudiro, Syawal; Supramono, Supramono; Andadari, Roos Kities; Sasongko, Gatot (Technium Business and Management, 2024)
The decision of prospective students to choose a tourism college in Yogyakarta is important to study. This aims to ensure that universities can provide the best service by selecting locations and improving facilities, the quality of human resources, and the image of universities. The growth of the tourism sector continues to increase, along with the increase in the number of tourist trips, so superior and professional resource personnel are needed. As educational institutions, tourism universities are responsible for producing quality and competitive human resources. The aim of this research is to analyze the influence of place and resource resources on student decisions through the image of the institution as a mediator. The research results show that the place and resources of the speakers do not directly have a significant influence on student decisions, but when mediated by the image of the institution, they have a significant influence. Furthermore, the place and resources of the speakers have a significant influence on the image of the institution, and the image of the institution also has a significant influence on student decisions. The research results show that institutional image is an important factor influencing student decisions.